2021
DOI: 10.1038/s41598-021-00927-x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of neutrophil-to-lymphocyte ratio in COVID-19 compared with Influenza and respiratory syncytial virus infection

Abstract: A high neutrophil to lymphocyte ratio (NLR) is considered an unfavorable prognostic factor in various diseases, including COVID-19. The prognostic value of NLR in other respiratory viral infections, such as Influenza, has not hitherto been extensively studied. We aimed to compare the prognostic value of NLR in COVID-19, Influenza and Respiratory Syncytial Virus infection (RSV). A retrospective cohort of COVID-19, Influenza and RSV patients admitted to the Tel Aviv Medical Center from January 2010 to October 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
52
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 48 publications
8
52
3
1
Order By: Relevance
“…However, inflammation parameters (CRP, lymphopenia), LDH—as a tissue injury parameter—and CK were significantly elevated in patients with COVID-19 pneumonia, contrary to normal CXR findings. In addition, previous studies reported that the neutrophile-to-lymphocyte ratio (NLR) was an independent risk factor for COVID-19 severity [ 25 , 26 ], which we observed to be significantly higher in patients with COVID-19 pneumonia.…”
Section: Discussionsupporting
confidence: 57%
“…However, inflammation parameters (CRP, lymphopenia), LDH—as a tissue injury parameter—and CK were significantly elevated in patients with COVID-19 pneumonia, contrary to normal CXR findings. In addition, previous studies reported that the neutrophile-to-lymphocyte ratio (NLR) was an independent risk factor for COVID-19 severity [ 25 , 26 ], which we observed to be significantly higher in patients with COVID-19 pneumonia.…”
Section: Discussionsupporting
confidence: 57%
“…However, many reports have identified NLR, dNLR, MLR as independent risk factors for severe disease [ 8 , 11 , 25 , 28 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…NLR is related to systemic inflammatory status and disease activity and has prognostic value in cardiovascular disease, autoimmune disease, tumors, and other infectious diseases [ 33 , 34 , 35 ]. NLR is also included as a variable in a risk score to predict the occurrence of critical illness in patients with COVID-19, and some studies have identified its role in discriminating severe disease and predicting mortality [ 8 , 11 , 25 , 31 , 32 , 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several viruses were found to upregulate host neutrophil/lymphocyte ratio (NLR), by promoting lymphopenia, associated with both COVID-19 critical illness and AD ( Kuyumcu et al., 2012 ; Sayed et al., 2020 ; Prozan et al., 2021 ). Elevated NLR likely reflects arginase upregulation and the subsequent depletion of arginine and nitric oxide (NO).…”
Section: Cell-cell Fusion the Molecular Actorsmentioning
confidence: 99%